How to lose a goblin in ten days - Sylva, Jessie (Tales from Hawthorne Cottage, 2026)
"When a halfling, Pansy, and a goblin, Ren, each think they've inherited the same cottage, they make a bargain: they'll live in the house together and whoever is driven out first forfeits their ownership. Amidst forced proximity and cultural misunderstandings, the two begin to fall in love. But when the cottage - and their communities - are threatened by a common enemy, the duo must learn to trust each other, and convince goblins and halflings to band together to oust the tall intruder."--